2006
DOI: 10.1080/01971520500543988
|View full text |Cite
|
Sign up to set email alerts
|

Improved Energy and Material Efficiency Using New Tools for Global Optimisation of Residue Material Flows

Abstract: Residue materials generated in the metallurgical industry have gained an increasing importance, both from the points of view of energy and material supply. A joint process integration model for the integrated steel plant system is developed and used in this paper. It takes into account both residue materials and energy recirculation for the system. The potential for increased recirculation and the effect on the system from an environmental point of view is presented, and implementations and practical experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The methodological approach applied in this and the previous cited works included standard techniques, modeling and simulation tools, and optimization techniques. This allows assessing different scenarios in a holistic way: as already proved in different works, the combination of well‐known analyses with modeling and simulation tools allows accounting the main and the most “hidden” aspects of a process/system or unit configuration in the evaluation of modifications of standard operating conditions or in the assessment of new scenarios. Furthermore, by combining coproducts, by‐products, and waste management simulations and optimization, the more suitable procedures for their potential internal or external recovery can be identified.…”
Section: Methodsmentioning
confidence: 96%
“…The methodological approach applied in this and the previous cited works included standard techniques, modeling and simulation tools, and optimization techniques. This allows assessing different scenarios in a holistic way: as already proved in different works, the combination of well‐known analyses with modeling and simulation tools allows accounting the main and the most “hidden” aspects of a process/system or unit configuration in the evaluation of modifications of standard operating conditions or in the assessment of new scenarios. Furthermore, by combining coproducts, by‐products, and waste management simulations and optimization, the more suitable procedures for their potential internal or external recovery can be identified.…”
Section: Methodsmentioning
confidence: 96%
“…Another application was the reduction of landfill by optimizing recycled material flows and burden materials for BF and BOF in 2006. It was found that, e.g., BOF slag recycling to the BF and increasing scrap load in BOF decrease landfill and lime use in the BF while also decreasing the BF hot metal yield.…”
Section: Integrated System Optimization and Designmentioning
confidence: 99%
“…Based on the mixed integer linear programming (MILP) combined with ReMIND [5] and CPLEX [6], mathematical process integration models of steelmaking industries have been developed in our research groups. The developed model has been successfully applied, for example to give suggestions on choosing a new blast furnace, to reduce the CO 2 emission by using alternative production routines, etc [7,8]. Recently, the research work has been extended to mining industries also [9,10].…”
Section: Introductionmentioning
confidence: 99%